Oxygen metabolism analysis of a single organoid for non-invasive discrimination of cancer subpopulations with different growth capabilities - Nashimoto, Yuji; Shishido, Shotaro; Onuma, Kunishige; Ino, Kosuke; Inoue, Masahiro; Shiku, Hitoshi (Frontiers in Bioengineering and Biotechnology, 2023)
A heterogeneous nature is a pivotal aspect of cancer, rendering treatment problematic and frequently resulting in recurrence. Advanced techniques for identifying subpopulations from a tumor in an intact state are necessary to develop a novel screening platform, revealing differences in treatment response among subpopulations. Herein, we conducted a noninvasive analysis of oxygen metabolism for multiple subpopulations in patient-derived organoids, examining the potential utility for the non-destructive identification of subpopulations based on oxygen metabolism. We utilized scanning electrochemical microscopy (SECM) as the noninvasive oxygen metabolism analysis. For the models of tumors with heterogeneous subpopulations, we used patient-derived cancer organoids with distinct growth potentials established by cancer tissue-originated spheroid (CTOS) methodology. SECM measurement realized the analysis of oxygen consumption rate (OCR) for individual organoids as small as 100 µm in diameter and could detect the heterogeneity among the subpopulations, which was not observed in conventional colorectal cancer cell lines. Further, through the OCR analysis for pre-isolated subpopulations with slow growth potentials, we unveiled that the OCR may reflect the difference in the growth speed of each organoid. Although our current technique lacks single-cell level sensitivity, the difference in oxygen metabolism between the subpopulation would be an important indicator for the future isolation of tumor subpopulations and the construction of a new drug screening platform.